Psychiatric Aspects of Obesity, Behavior and Cognitive Behavior Therapy in Treatment - Gulin Ozdamar Unal (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Obesity is a multifactorial condition associated with psychological and social factors. Studies have shown that obese individuals have higher rates of mental illnesses compared to the general population. Treatment of obesity has improved both physical health and mental health. The addition of behavioral therapies to lifestyle changes in the treatment of obesity increases the effectiveness of the treatment and contributes to the maintenance of the target weight. In this article, the effects of obesity on epidemiological characteristics, physical and mental health, behavioral and cognitive behavioral therapy applications are presented. [JCBPR 2018; 7(1.000): 31-41]